ANALISIS PENGARUH STRUKTUR PASAR DAN RASIO KEUANGAN TERHADAP PROFITABILITAS BANK UMUM KONVENSIONAL DI INDONESIA TAHUN 2009-2013 - Indra Aurum, M. Rizki; Sampurno, R. Djoko (Diponegoro Journal of Management, 2015)
This study aimed to examine the effect of variable market shareÂ  and the level of concentration (concentration rate) as a proxy of market structure and bank financial ratios such as Net Interest Margin (NIM), Capital Adequacy Ratio (CAR), the Loan to Deposit Ratio (LDR ), and Operating Expenses Operating Income (BOPO) on the profitability of commercial banks.This study uses data obtained from the annual financial statements published by the bank in the Condensed Financial Statements Financial Services Authority. The population in this study are120 commercial banks listed on the FSA between 2009 and 2013. The samples used with judgment sampling as many as 20 commercial banks with the largest amount of assets. Data analysis methods used in this research is panel data regression with Fixed Effect Method (FEM). Hypothesis test using t-test to test the effect of individual variables, as well as the F-test to test the effect of variables simultaneously with a significance level of 5%. The results showed that the structure of the banking industry in Indonesia in 2009-2013 led to the traditional hypothesis, which profitability affected by market concentration. Market share has positive effect and not significant on profitability. NIM and CAR have positive effect and significant positive effect on profitability, while LDR and BOPO have negative effect and significant on profitability.